Thymic mucosa-associated lymphoid tissue lymphoma in a patient with Sjögren’s syndrome with cutaneous vasculitis - Božić, Ksenija; Živojinović, Dragan; Djenić, Ljubinko; Atanasković, Lavinika (Vojnosanitetski pregled, 2024)
Introduction. The association between Sjögren’s syndrome (SS) and the development of lymphoma is well known. The prevalence of lymphoma in patients with SS is 5%. Mucosa-associated lymphoid tissue (MALT) lymphoma is the most common lymphoma type in patients with SS. It is common for MALT lymphoma to develop in the stomach, while it is extremely rare in the thymus. Case report. We present a 61-year-old Caucasian male patient with primary SS, cutaneous vasculitis, and thymic MALT lymphoma. The patient had a two-year history of diffuse cutaneous palpable purpura on legs, intermittently enlarged left parotid gland, and dry mouth. The results of Schirmer’s test were positive, labial salivary glands biopsy revealed a focus score ≥ 1, serology testing showed positive anti-Ro/SS-A and anti-La/SS-B antibodies, while skin biopsy findings revealed leukocytoclastic vasculitis. Diagnosis of primary SS with extraglandular cutaneous manifestations was confirmed. Cryoglobulinemia (Cg) and monoclonal gammopathy (MG) were detected, which increased the suspicion of hematological malignancy, and additional diagnostic procedures were performed. Computed tomography of the chest revealed an enlarged, multicystically altered anterior mediastinal mass. A thymectomy was performed through video-assisted thoracic surgery. Histological findings of the tissue confirmed the presence of tumor tissue consistent with MALT lymphoma in the thymus. Induction therapy with pulse doses of glucocorticoids was applied for three days, which was continued with medium doses of the drug. The doses were gradually reduced, and hydroxychloroquine was introduced. This has shown to be an effective therapy against features of SS. Postoperative local radiotherapy was performed. Conclusion. In SS patients with CV and in the presence of Cg and MG, attention should also be paid to the eventual development of MALT lymphoma, including the rare localization in the thymus.